Cystatin C, Renal Function and Atherosclerosis in Rheumatoid Arthritis - Lertnawapan, Ratchaya (2011)
OBJECTIVE: We examined the hypothesis that cystatin C, a novel marker of renal function, is elevated in rheumatoidarthritis (RA) and associated with inflammation and coronary atherosclerosis. METHODS: We measured serum cystatin C, creatinine, TNF-α and IL-6 concentrations, coronary artery calcium score (CACS), and Modified Diet in Renal Disease estimated GFR (MDRD-eGFR) in 167 patients with RA and 91 controls. RESULTS: Cystatin C was higher in RA (median [IQR]: 1.16 [0.99–1.35] mg/L) than controls (1.01 [0.90–1.19] mg/L), (P<0.001) and positively correlated with ESR (P<0.001), CRP (P=0.01), DAS28 (P=0.006), and Framingham risk score (FRS)(P=0.02). Cystatin C was correlated with CACS (P<0.001) in RA, but this was not significant after adjustment for age, race, sex and FRS (P =0.44). CONCLUSIONS: Cystatin C concentrations are higher in RA than controls and may reflect inflammation and undetected subclinical renal dysfunction. Cystatin C provides information regarding the risk of atherosclerosis in RA, but this is linked to conventional cardiovascular risk factors.